TRPC6 regulates phenotypic switching of vascular smooth muscle cells through plasma membrane potential‐dependent coupling with PTEN. Issue 9 (4th June 2019) - Numaga‐Tomita, Takuro; Shimauchi, Tsukasa; Oda, Sayaka; Tanaka, Tomohiro; Nishiyama, Kazuhiro; Nishimura, Akiyuki; Birnbaumer, Lutz; Mori, Yasuo; Nishida, Motohiro
ABSTRACT: Vascular smooth muscle cells (VSMCs) play critical roles in the stability and tonic regulation of vascular homeostasis. VSMCs can switch back and forth between highly proliferative synthetic and fully differentiated contractile phenotypes in response to changes in the vessel environment. Although abnormal phenotypic switching of VSMCs is a hallmark of vascular disorders such as atherosclerosis and restenosis after angioplasty, how control of VSMC phenotypic switching is dysregulated in pathologic conditions remains obscure. We found that inhibition of canonical transient receptor potential 6 (TRPC6) channels facilitated contractile differentiation of VSMCs through plasma membrane hyperpolarization. TRPC6‐deficient VSMCs exhibited more polarized resting membrane potentials and higher protein kinase B (Akt) activity than wild‐type VSMCs in response to TGF‐β1 stimulation. Ischemic stress elicited by oxygen‐glucose deprivation suppressed TGF‐β1‐induced hyperpolarization and VSMC differentiation, but this effect was abolished by TRPC6 deletion. TRPC6‐mediated Ca 2+ influx and depolarization coordinately promoted the interaction of TRPC6 with lipid phosphatase and tensin homolog deleted from chromosome 10 (PTEN), a negative regulator of Akt activation. Given the marked up‐regulation of TRPC6 observed in vascular disorders, our findings suggest that attenuation of TRPC6 channel activity in pathologic VSMCs could be a rational strategy to maintain vascular quality control by fine‐tuning of VSMC phenotypic switching.—Numaga‐Tomita, T., Shimauchi, T., Oda, S., Tanaka, T., Nishiyama, K., Nishimura, A., Birnbaumer, L., Mori, Y., Nishida, M. TRPC6 regulates phenotypic switching of vascular smooth muscle cells through plasma membrane potential‐dependent coupling with PTEN. FASEB J. 33, 9785–9796 (2019). www.fasebj.org